Analysis Mix Marketing : Building an Attractive Destination Image in SoE City - Watu, Engelbertus Glory Christy; Fallo, Apryanus; Lopes Amaral, Maria Augustin; Ketmoen, Adrianus (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
This research aims to explore the relationship between marketing mix, memorable tourism experience (ME), destination image, tourist satisfaction, and intention to return to the destinations of Oetune Beach, Oehala Waterfall, and Bu'at Recreation Park. The research method uses a quantitative approach by distributing questionnaires to a sample of tourists visiting the destination. The results of the analysis show that marketing mix, ME, and destination image have a significant effect on tourist satisfaction. Apart from that, destination image also has a direct influence on intention to visit again, while tourist satisfaction acts as a mediator between the marketing mix, ME, and destination image variables and intention to visit again. The practical implication of these findings is the need for holistic destination management, with a focus on improving the quality of tourism experiences and building a positive destination image through effective marketing strategies.